Propionic acidaemia crisis: a specific DWI finding-case report - Khairy Abdella (SpringerOpen, 2023)
Abstract Background Propionic acidaemia is among the rarest metabolic disorders described in the literatures. It has resulted from an inborn error in the catabolism of amino acids with an accumulation of organic acids as a consequence of this error. This illness was especially manifested and discovered in early postnatal life with other forms seen later in the childhood period. It has different clinical presentations with poor feeding, hypotonia, and lethargy described in the early neonatal period, while mental retardation, global developmental delay, and seizures are seen in childhood. Case presentation We present a case of a 4-month-old child already diagnosed in his early neonatal period with propionic acidaemia currently presented with propionic acidaemic crisis in the form of frequent attack of seizures and severe hyperammonemia with unique DWI features which shows bilateral symmetrical restricted diffusion in the subcortical and subinsular white matter that are specific to propionic acidaemia crisis and does not relate to any vascular territory. Conclusion Propionic acidaemia is one of the rarest metabolic disorders reported in both early neonatal life and the childhood period. Understanding the clinical presentation and MRI findings with specific DWI changes reported in this case assists the health care provider in making the appropriate clinical management and metabolic screening decisions. This case with these rare and specific DWI changes seems to be unique to the propionic acidaemia crisis which reinforces MRI findings and changes mentioned previously in the literatures.